Estrategia para escribir un texto descriptivo en estudiantes de tercer grado de Educación Primaria - De la Cruz Marchena, Erika Isidia (2021)
The present study was carried out with the purpose of executing strategies to write a descriptive text by students of third grade of primary education, which was carried out in 24 students of third grade "A", in them the strategies of planning, adequacy, coherence, correction, and creativity were taken into account, taking into account the competences of the area of communication skills and performances that the students should achieve. In addition, three fundamental aspects must be taken into account in any descriptive text, according to Schökel (1972), observation, order and execution are the most important for a good presentation of what is to be described. At the end of the session there were good results, most of the students carried out their description of their text on an endangered animal, achieving 87.5% (21 students) at the achieved level and 12.5% (3 students) at the level in process. It is concluded that according to the primary level, the subject of the description should be mentioned to facilitate its description in the student, in communication the description is important for the reader to make an evaluative judgment of the description of the text.